David's Successors : Kingship in the Old Testament - Galvin, Garrett, 1968- (Book collections on Project MUSE., 2016)
David's Successors: Kingship in the Old Testament argues for a new reading of kingship in the Old Testament. Rather than presenting the kings as monsters -- with the occasional angelic ruler -- this study seeks a more nuanced version of kingship. This book considers the original concept and context of kingship before concentrating on five kings in particular: Jeroboam, Ahab, Hezekiah, Manasseh, and Josiah. Much contemporary scholarship is concerned with the reconceptualization and recontextualization of kingship that hearkens from a negative perspective on kingship, but this book will fully consider the positive and original vision of kingship. This book is ultimately rooted in a hopeful and joyful view of humanity as found in the Psalms, Sirach, and the Chronicles.